The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/s40623-014-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspect angle sensitivity of pump-induced optical emissions at EISCAT

Abstract: We investigate the aspect angle sensitivity of the pump-induced artificial optical emissions in the ionosphere over the European Incoherent Scatter Scientific Association (EISCAT) high-frequency transmitter facility at Ramfjord, Norway, as a function of the pump beam launch angle relative to the magnetic field line direction. The highest intensity optical emissions occur when the pump beam pointing direction is in the magnetic zenith (approximately 12°S of local zenith). For pump beam directions further north … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Outside this angular range, optical emissions were effectively not observed. Kosch et al [2014a] confirmed this scenario at EISCAT, and likewise Shindin et al [2015] at SURA, albeit for a more limited region around the magnetic zenith. Kosch et al [2014a] also found that the optical emission always maximized in the magnetic zenith provided any pump power went in this direction.…”
Section: Magnetic Aspect Angle Effectssupporting
confidence: 77%
See 1 more Smart Citation
“…Outside this angular range, optical emissions were effectively not observed. Kosch et al [2014a] confirmed this scenario at EISCAT, and likewise Shindin et al [2015] at SURA, albeit for a more limited region around the magnetic zenith. Kosch et al [2014a] also found that the optical emission always maximized in the magnetic zenith provided any pump power went in this direction.…”
Section: Magnetic Aspect Angle Effectssupporting
confidence: 77%
“…Kosch et al [2014a] confirmed this scenario at EISCAT, and likewise Shindin et al [2015] at SURA, albeit for a more limited region around the magnetic zenith. Kosch et al [2014a] also found that the optical emission always maximized in the magnetic zenith provided any pump power went in this direction. Consistent with the optical observations, the pump-induced electron temperature enhancements, observed by the EISCAT incoherent scatter radar, also maximized in the magnetic zenith [Rietveld et al, 2003].…”
Section: Magnetic Aspect Angle Effectssupporting
confidence: 77%
“…The upper atmospheric science community has access to a large number of high power HF transmitters used to modify the F region ionosphere. These include SURA in Russia [ Belikovich et al, ], European Incoherent Scatter (EISCAT) Heating in Norway [ Kosch et al, ], and the soon to be operational Arecibo HF facility in Puerto Rico. Each facility has unique capabilities because of their location with ambient electron densities that tend to be larger at lower latitudes and the inclination of the magnetic field which ranges from horizontal at the equator to nearly vertical at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant discovery was the fact that several HF‐induced phenomena in the F region are especially strong when pumping in the magnetic field‐aligned direction. For example, the optical emissions [ Kosch et al ., , ], electron heating [ Rietveld et al ., , ], and ion upwelling [ Kosch et al ., ] all are strongest when the HF beam is pointed along the magnetic field. The discovery of artificial ionization in recent years, which at HAARP has been detected as artificial layers, is discussed in detail by Mishin et al .…”
Section: Overview Of Scientific Results Utilizing Powerful Hf Waves Amentioning
confidence: 99%